ELECTRONIC STUDY BOOKS TO CREATE ANALYSIS TO DO - Sultanova Dildora Ilhomjon daughter; Bakhromov Fazliddin Lutpiddin son (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Annotation . Electronic study literature in creating education process for individualization enable gives , training process own himself control to do and observation opportunity gives , har different optimal solution in cases acceptance to do teaches , it is known type thought to keep develops knowledge get culture forms . Electronic study literature apply and Create problems learning main is considered